Anodic TiO2 nanotube walls reconstructed: Inner wall replaced by ALD TiO2 coating - Motola, Martin; Zazpe Mendioroz, Raúl; Hromádko, Luděk; Přikryl, Jan; Čičmancová, Veronika; Rodriguez Pereira, Jhonatan; Sopha, Hanna Ingrid; Macák, Jan (Elsevier, 2021)
A reconstruction process of TiO2 nanotube (TNT) layers towards their superior photoelectrochemical performance and photocatalytic activity is presented. At first, TNT layers (similar to 5 mu m thick, similar to 250 nm in diameter) were prepared via electrochemical anodization to obtain double-wall (DW) TNT layers. Second, a selective chemical treatment was conducted to etch the inner wall, yielding single-wall (SW) TNT layers. Third, TNT layers were coated by an additional approx. 5.5 nm, 11 nm, and 16 nm thick TiO2 coatings, respectively, using Atomic Layer Deposition (ALD). A pronounced increase in the incident photon-to-electron conversion efficiency (reaching similar to 85% at lambda - 350 nm) was achieved on SW TNT layers coated with 11 nm thick ALD coatings compared to SW without coating (similar to 35% at lambda = 350 nm). This is due to the optimal thickness of the ALD TiO2 coating that passivates surface states and improves the separation of the photogenerated charge carriers. Photocatalytic performance of SW TNT layers with 11 nm thick ALD coatings (rate constant; k = 0.1156 min(-1)) was increased by approx. 10-times compared to that of the nowadays most reported blank DW TNT layers (rate constant; k = 0.0119 min(-1)).

A reconstruction process of TiO2 nanotube (TNT) layers towards their superior photoelectrochemical performance and photocatalytic activity is presented. At first, TNT layers (similar to 5 mu m thick, similar to 250 nm in diameter) were prepared via electrochemical anodization to obtain double-wall (DW) TNT layers. Second, a selective chemical treatment was conducted to etch the inner wall, yielding single-wall (SW) TNT layers. Third, TNT layers were coated by an additional approx. 5.5 nm, 11 nm, and 16 nm thick TiO2 coatings, respectively, using Atomic Layer Deposition (ALD). A pronounced increase in the incident photon-to-electron conversion efficiency (reaching similar to 85% at lambda - 350 nm) was achieved on SW TNT layers coated with 11 nm thick ALD coatings compared to SW without coating (similar to 35% at lambda = 350 nm). This is due to the optimal thickness of the ALD TiO2 coating that passivates surface states and improves the separation of the photogenerated charge carriers. Photocatalytic performance of SW TNT layers with 11 nm thick ALD coatings (rate constant; k = 0.1156 min(-1)) was increased by approx. 10-times compared to that of the nowadays most reported blank DW TNT layers (rate constant; k = 0.0119 min(-1)).
Anodic TiO2 nanotube walls reconstructed: Inner wall replaced by ALD TiO2 coating
Keywords: TiO2 nanotube layers; Single-wall; Atomic layer deposition; Photoelectrochemistry; Photocatalysis; TiO2 nanotube layers; Single-wall; Atomic layer deposition; Photoelectrochemistry; Photocatalysis